Inflow cannula obstruction in Berlin Heart Excor and novel extracorporeal membrane oxygenation cannulation for rescue. Issue 9 (September 2020) - Deshpande, Shriprasad R; Desai, Manan; Sinha, Pranava; Kanter, Joshua; Yerebakan, Can
Utilization of Berlin Excor as a pediatric bridge to transplantation device continues to increase. Thromboembolic complications continue to be an important morbidity related to ventricular assist devices. Obstructions to the device cannulae are rare but potentially life-threatening complications of ventricular assist devices, but inflow cannula obstruction is hitherto unreported. We present a case of a 4-year-old supported with Berlin BiVAD who demonstrated acute decompensation related to thrombus within the left atrial cannula. We describe the diagnosis, intervention, as well as novel rescue using existing cannulae for extracorporeal membrane oxygenation support.